LEGAL ASPECT OF FOREST FIRE IN INDONESIA - Mohammad Taufik Makarao; Firly Fatharani Hafizha (VERITAS, 2020)
This study to examine legal aspect, why always happen and impact of forest fire in Indonesia. The conclusion are, even though there is a forestry law as regulated in Law No. 41/1999 on Forestry, as amended by Law Number 19/2004, forest fires have been repeated several large scale since the early 1980s until now. The case of Indonesia which was experiencing forest fires is a manifestation of unclear and poorly enforced policies, economic forces that push business to use fire to clear land, lack of technological alternatives, poor public participation and aggravated by climatic condition such as the extended drought. Although many policies have already been formulated and special management agencies have been established, policies implementation remain weak, coordination is poor and the current system is inefficient. Added to these factors, is the reality that government official’s business leader and general public lack a sense of urgency about the fires. Fires can impede national economic performance and increase poverty at the local level. It is mostly that disaster until now will repeat/recur unless definitive steps are taken to encourage short term and long term prevention strategies. Fires cause tremendous ecological impacts such as air quality, hydrological cycle, biological diversity, natural succession, disruption of the production and decomposition of organic materials, soil, disruption in the nutrient cycle, climate regulation and carbon sink; social impact such as food security, impact on health such as death, asthma, ARI, and impact on economic such as, agriculture, forestry, health, transmigration, transportation and tourism.